The Intervention e ect Focus alternatives or inde nite alternatives? Experimental evidence - Haida, Andreas; Repp, Sophie (Proceedings of the Amsterdam Colloquium, 2013)
In many languages, quantificational and focusing elements may not intervene between a wh-phrase and the interrogative complementizer by which it is licensed. Among the semantic approaches to explaining this phenomenon, there are two that make different predictions as to the intervener status of focus particles. According to the first approach, all focus particles are interveners. According to the second approach, only and even are in interveners while also is not. We present evidence from two speeded-acceptability judgement experiments and a self-paced reading experiment in German which tested the acceptability and online processing of intervention sentences with only and also with regard to the predictions of the two theories. The results of the three experiments converge in showing that also is not an intervener in German. We argue that this can be taken as evidence for theories where focus is not the key property in the emergence of the intervention effect, at least for German.